Forecasting and estimation of medical tourism demand in India - Ahire, Manoj Popatrao (2020)
The paper deals with India’s Medical tourism analysis and forecasting, apply-ing two time series forecasting models, for monthly data spreading over 2014 to 2017. Medical tourism worldwide and particularly in India is on rise. Fig-ures of medical tourist arrivals in India for 2014, 2015 and 2016 denotes a significant growth. Several measures have been taken by the Government to attract medical tourists to the country. This study was undertaken to analyse the growth trends in medical tourism in India over a period of last four years and to forecast the medical tourist arrivals over the next couple of years us-ing the ARIMA method for trend projection. The paper discusses these trends and the application of the model. The projections show a great poten-tial for the country to earn valuable foreign exchange through medical tour-ism. India has a huge cost and expertise advantage which if leveraged through proper publicity can make it one of the leading medical tourist des-tinations in the days to come. It is suggested that the authorities should take efforts in this direction with aggressive publicity policies.